ANALYSIS OF COMPENSATION AND WORKING ENVIRONMENT ON LECTURER PERFORMANCE AT AL AZHAR UNIVERSITY MEDAN - Saidan Sany Lubis; Yeni Absah; Vivi Gusrini Rahmadani Pohan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The purpose of this study was to evaluate various aspects of the performance of lecturers at Al Azhar University Medan in terms of compensation and work environment. The population used is all lecturers of Al Azhar University Medan with the sample used using Slovin totaling 54 people. The data analysis technique used is using the classical assumption test consisting of (normality, heterocedacity, multicolonierity), multiple linear regression test, t test, f test and determination test using SPSS (Statistical Package for the Social Sciences). The results of this study indicate that 1) Compensation has a positive and significant effect on Lecturer Performance, 2) Work Environment has no effect and is not significant to Lecturer Performance, 3) Compensation and Work Environment affect Lecturer Performance simultaneously.